2018
DOI: 10.1161/circresaha.117.311522
|View full text |Cite
|
Sign up to set email alerts
|

Down Syndrome Critical Region 1 Gene, Rcan1 , Helps Maintain a More Fused Mitochondrial Network

Abstract: RCAN1 helps maintain a more interconnected mitochondrial network, and maintaining appropriate RCAN1 levels is important to human health and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 52 publications
6
57
0
Order By: Relevance
“…We have recently shown that loss of RCAN1 increases calcineurin-dependent mitochondrial fission both in vitro and in vivo [78]. Consistent with increased fission, we found that mitochondrial membrane potential and oxygen consumption were lower in myocytes and fibroblasts isolated from Rcan1-KO mice.…”
Section: Rcan1 Acts In Multiple Tissuessupporting
confidence: 86%
“…We have recently shown that loss of RCAN1 increases calcineurin-dependent mitochondrial fission both in vitro and in vivo [78]. Consistent with increased fission, we found that mitochondrial membrane potential and oxygen consumption were lower in myocytes and fibroblasts isolated from Rcan1-KO mice.…”
Section: Rcan1 Acts In Multiple Tissuessupporting
confidence: 86%
“…Several lines of evidence suggest that RCAN1 is involved in the regulation of mitochondrial function in different cell types [19][20][21]. However, the role of RCAN1 in renal cells is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…RCAN1 overexpression also promotes age-dependent mitochondrial dysregulation and progressive neurodegeneration in Alzheimer's disease [20]. On the other hand, mitochondrial function is reduced in cardiomyocytes depleted of RCAN1, and increasing RCAN1.1 level helps maintain a more fused mitochondrial network and increase O 2 consumption [21]. These contrary regulatory effects suggest that more in-depth studies are needed on how RCAN1 works.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AAC could influence cell death through a cooperation with pro-apoptotic proteins, such as Bax, or through its participation in the MPTP complex [ 64 , 77 ]. Alteration of AAC activity has been reported in Drosophila nebula mutants [ 78 , 79 ] Nebula is the Drosophila homolog of human Down syndrome critical region gene 1 (DSCR1), one of the genes involved in the establishment of the phenotype associated with Down syndrome. DSCR1 overexpression in Down syndrome fetal brain tissue seems to contribute to mental retardation in Down syndrome patients.…”
Section: Drosophila Melanogaster Vs Human Mitomentioning
confidence: 99%